Searching for Central America’s “Rebel Archives” and Communist Histories: Notes from the Field - Cárcamo , Jennifer A. (2024)
Building on and from my experience conducting archival research during the covid-19 pandemic on Central American communists in Cuba, Russia, Mexico, and El Salvador, I argue that the archive is a site of political struggle wherein scholars and historians play a significant role in determining what is remembered and, equally important, what is forgotten, especially when it comes to radical and communist histories of/from Central America. I begin by analyzing the works of scholars who informed and shaped my transnational analysis and approach to conducting historical archival research, including scholars of Central America, and then share my personal experience navigating archives during a particularly heightened political climate in four different countries with controversial and fragile US relations.